2a+6=a-7

Simple and best practice solution for 2a+6=a-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a+6=a-7 equation:



2a+6=a-7
We move all terms to the left:
2a+6-(a-7)=0
We get rid of parentheses
2a-a+7+6=0
We add all the numbers together, and all the variables
a+13=0
We move all terms containing a to the left, all other terms to the right
a=-13

You can always share this solution

See similar equations:

| 5x+8-12x=-6x-2x-3 | | 6(2r-1)=-78 | | f(1/2)=2(1/2)+3 | | -(3x+-12)=48 | | -1n+10=3 | | 4(x?5)+2=4x?18 | | x-3/3=-4/1/2X3 | | (1.4)x=8 | | (x-9)^2=49 | | z/3+3=8/3 | | -x÷9=-8 | | ?1+5x?15=?7(?6+8x)+3 | | 8+32y=24 | | 198=68-10x | | 16+2p=20 | | -29=7v+4(-8v-1) | | 3x-3x=17-5 | | x2?125=0 | | -2(x+3)=5(x+1) | | 0=x^2-2x-28 | | 2x+5(18)=6x | | -3(4x+3)+4*6x+1)=43 | | 4r+1=?2r+8 | | -1(3x+-12)=48 | | 116=4(5-6x) | | -5(5x-5)+3=-25x+28 | | 7c+12=-4c(78+12) | | 16x^2-56x+37=0 | | 1/4+x-1/3=2/3+3+1/4 | | -1/4w=7 | | 33=4x-7x+6 | | 4=4(x+3) | | 25=-2(5h+3) | | (6^x)=(1/216) | | x^2+22x=8 | | 2+2(3x-4)=8x | | |-3r|=9 | | 69=1+2(4-5x) | | F(x)=-3+4 | | |3x|=9 | | 1.5(x+4)–3=4.5(x–2) | | 2x?2???28x+98=0 | | ?4=x/20?5 | | 9.34=x-2.7 | | 3(5b+5)+6=81 | | 6x-14=-2x+10 | | 8-8(7n-7)=176 | | 12x+1=3(4x+1)–2 | | 3(h+4)=18 | | 2(x-5)^2=-32 | | 124=4(1+5a) | | Y=-3/2x+8 | | 16-10=4q | | 2x+3-4x+7=5 | | 6w-8=4w+2 | | 1/4x+1/2=13 | | 7/12=3/x | | 2s+s=10 | | 9/8=g+(1/2) | | 13x=63 | | (2x-3)^2=0 | | X^2-0.6x+0.09=29.16 | | 7/6=x/8+5/8 | | -3x+12=-21+8x | | -2=-2x^2-3x |